Management of Honesty Canteen: Study of Cultural Capital in Economic Activities - Suharnanik, Suharnanik; Budiono, Sucahyo Tri (Budapest International Research and Critics University, 2020)
An economic activity has a system that is structured quickly and systematically, but what is in the canteen is honesty. An activity that only requires goods to be sold provides a place for payment, writes down the price of the goods to be sold, then the buyer comes to that place. A simple economic activity with no salesperson, no supervision and no cashier. This research is analyzed based on the facts that occur in several places that have honesty canteens, for example in the campus environment and schools where the seller of the honesty canteen is still in the research stage of who and what the seller is like. This research method uses qualitative research which prioritizes data collection by means of in-depth interviews. Direct observation with in-depth observation on what kind of place, the symbols of existing values, and the values adopted in the honesty canteen. The results of this study found that honesty is an economic activity based on belief in the form of slogans, teachings contained in religious values. Because of these religious values, the canteen of honesty has become a belief-based economic activity. This model of formation of economic activity is based on mutual trust between sellers and buyers. The results of this study consider economic activities that run and go well in a social environment that has strict adherence to religious teachings.